Intraoperative Assessment of the Resection Specimen Facilitates Achievement of Adequate Margins in Oral Carcinoma - Smits, Roeland W. H.; van Lanschot, Cornelia G. F.; Aaboubout, Yassine; de Ridder, Maria; Hegt, Vincent Noordhoek; Barroso, Elisa M.; Meeuwis, Cees A.; Sewnaik, Aniel; Hardillo, Jose A.; Monserez, Dominiek; Keereweer, Stijn; Mast, Hetty; et al. (Frontiers in Oncology, 2020)
Background Inadequate resection margins in oral cavity squamous cell carcinoma have an adverse effect on patient outcome. Intraoperative assessment provides immediate feedback enabling the surgeon to achieve adequate resection margins. The goal of this study was to evaluate the value of specimen-driven intraoperative assessment by comparing the margin status in the period before and the period after the introduction of specimen-driven assessment as a standard of care (period 2010–2012 vs period 2013–2017). Methods A cohort of patients surgically treated for oral squamous cell carcinoma at the Erasmus MC Cancer Institute, Rotterdam, between 2010–2012 was studied retrospectively and compared to results of a prospectively collected cohort between 2013–2017. The frequency, type and results of intraoperative assessment of resection margins were analyzed. Results One hundred seventy-four patients were included from 2010–2012, 241 patients were included from 2013–2017. An increase in the frequency of specimen-driven assessment was seen between the two periods, from 5% in 2010–2012 to 34% in 2013–2017. When performing specimen-driven assessment, 16% tumor-positive resection margins were found in 2013–2017, compared to 43% tumor-positive resection margins overall in 2010–2012. We found a significant reduction of inadequate resection margins for specimen-driven intraoperative assessment (p < 0.001). Also, tumor recurrence significantly decreased, and disease-specific survival improved when performing specimen-driven intraoperative assessment. Conclusions Specimen-driven intraoperative assessment improves resection margins and consequently, the outcome of oral cancer patients. We advocate this method as standard of care.